THE REACTION OF PHOSPHORUS-CONTAINING INTRACELLULAR INCLUSIONS TO SPACE WEATHER CHANGES - Gromozova, E. N.; Kachur, T. L.; Voychuk, S. I.; Kharchuk, M. S. (Одеські астрономічні публікації, 2016)
It is known that the bio-astronomical effect of Chizhevsky-Velhover is based on the cytochemical metachromatic reaction of polyphosphatecontaining volutin granules of microorganisms. As a result of long-term monitoring (2001-2015 years) of this of cytochemical index in yeasts Saccharomyces cerevisiae, it was shown that metachromatic staining of the granules possessed rhythmicity and connection with space weather. Under laboratory conditions the change of metachromasy was achieved by applying different stress factors: anaerobiosis, low temperature, acidity. Simulation of metachromatic staining in vitro by using solutions of inorganic polyphosphate with other compounds showed that this reaction was possible for the low concentrations of these polymers. The effect of the low concentrations was more expressed with increasing chain length of polyphosphate. The inhibition of the metachromasy in solution with added protein and calcium chloride indicated that this of reaction involved the presence of the protonated sites in the polymers. It is assumed that metachromatic staining of volutin granules in vivo may depend on other conditions including conformational restructuring of a polymer or sol-gel phase transitions. Thus, the question whether the metachromatic reaction of intracellular polyphosphate granules to the space weather changes is driven by a response to associated stress or despite the apparent similarity of the effects they are of a different nature remains unclear.